Penyuluhan sebagai Strategi Peningkatan Pengetahuan Masyarakat tentang Dampak Sampah Plastik dan Pengelolaannya di Desa Panjangrejo Bantul Yogyakarta - Satar, Ibdal; Syamsuddin, Arief; Suharto, Totok Eka; Permadi, Adi; Widyaningrum, Trianik; Khakim, Mufti; Baswara, Ahmad Raditya Cahya; Setyanto, Barry Nur (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
Plastic waste has become a significant problem of environmental pollution in recent decades. The nature of plastic waste is complicated to decompose; it has worsened the environmental situation, especially if it is not taken seriously immediately. One approach that can be taken to overcome this problem is to provide counseling to the public so that they do not dispose of plastic waste carelessly. The community service program is a forum for academics to participate and provide counseling about the management of plastic waste. The purpose of this community service program is to counsel the Panjangrejo community about how to manage plastic waste properly. This counseling program began with discussions with the Panjangrejo sub-district officials and related parties, then continued with planning the timing of the extension. Residents and community elements are fully involved, so this program can run smoothly. The counseling program was carried out in three villages, namely the villages of Semampir, Gunung Puyuh, and Krapyak Wetan, and this program was held at night from 20.00 WIB to 22.00 WIB. The outreach results showed that people's knowledge about the dangers of plastic waste and how to manage it could be significantly improved (p < 0.05). In general, this extension program successfully increased respondents' knowledge from "not knowing" to "knowing better" about the dangers and how to manage plastic waste.